In the Trap of Post-Socialist Stagnation: On Political Development of the Belarusian Society in the Years 1986-2006 - Brzechczyn, Krzysztof (Peter Lang, 2009)
The aim of this paper is to analyze the political development of the Belarusian society in the years 1986–2006 in order to answer the following questions: (i) what was the impact of support the nomenclature of the Belarusian Communist Party gave to the Belarusian independence after August 1991 on the process of decrease in power regulation (or in other words – democratization), (ii) why initial period of decrease in power regulation was replaced by its growth and (iii) why this growth of power regulation did not encounter efficient civil reaction like in the neighbouring republics (ex. Ukraine). Finally, I would like to consider further political development in Belarus, especially the perspective of civil revolutions. Presented analysis will not be a chronicler’s presentation of facts from the current history of this country but will be based on a social theory – non–Marxian historical materialism, which will serve as a basis for answering these questions and considering posed problems.
Keywords: Non-Marxian historical materialism; Belarus; Democratization; Communism